The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/adm.0b013e31813872e4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Smoking Cessation Treatment Study at Substance Abuse Rehabilitation Programs: Smoking Behavior and Treatment Feasibility Across Varied Community-based Outpatient Programs

Abstract: Cigarette smoking is widely prevalent among individuals in treatment for drug or alcohol dependence; however, the treatment of nicotine addiction in this population has numerous obstacles at both programmatic and patient levels. Despite these difficulties, recent studies have demonstrated moderate success in implementing smoking cessation treatment in drug rehabilitation programs. The National Drug Abuse Treatment Clinical Trials Network sponsored a smoking cessation study in 13 community-based outpatient subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
2
19
1
Order By: Relevance
“…More outpatient programs originally signed up for the study but dropped out when recruitment proved infeasible (see Reid et al, 2007). The group treatment format, although favored by providers for its low cost of delivery, appeared to be one of the key barriers to enrollment because it did not suit patients' needs for flexibility of scheduling and may also have figured in the limited counseling adherence rates (Reid et al, 2007). The present design did not separate the contributions of the cognitive-behavioral/mood management counseling versus the nicotine replacement to smoking abstinence rates and reductions in smoking.…”
Section: Discussionmentioning
confidence: 99%
“…More outpatient programs originally signed up for the study but dropped out when recruitment proved infeasible (see Reid et al, 2007). The group treatment format, although favored by providers for its low cost of delivery, appeared to be one of the key barriers to enrollment because it did not suit patients' needs for flexibility of scheduling and may also have figured in the limited counseling adherence rates (Reid et al, 2007). The present design did not separate the contributions of the cognitive-behavioral/mood management counseling versus the nicotine replacement to smoking abstinence rates and reductions in smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The need for more effective interventions for smoking is especially pronounced among drug- and alcohol-dependent patients, the majority of whom smoke (70–90%) (7,8,9,10), and among whom smoking is associated with greater levels of substance abuse (7,10,11), nicotine dependence (12,13,14), medical problems (15,16), and mortality (17), and low abstinence rates (10% to 20%) in response to smoking cessation interventions (18,19,20,21,22,23,24,25,26,27,28). …”
Section: Introductionmentioning
confidence: 99%
“…As previously noted, the majority of women with mental illness or substance use disorders smoke; therefore, integrated approaches are required. Although it is a common belief among clinicians and others that people in treatment for mental health or substance use issues cannot quit smoking or would be at greater health risk if they tried to do so (Prochaska, 2010), evidence suggests that people in treatment for substance use, particularly women, are interested in quitting smoking (Poole, Greaves, & Cormier, 2003;Reid et al, 2007). Integrated treatments, including smoking cessation interventions provided concurrently during addictions treatment (Prochaska, Delucchi, & Hall, 2004) and mental health services (McFall et al, 2010;Prochaska, 2010), have been shown to enhance the effectiveness of treatment.…”
Section: Integrated Approaches To Mental Health Substance Use and Smentioning
confidence: 99%